Searching for an Added Value of Precipitation in Downscaled Seasonal Hindcasts over East Africa: COSMO-CLM Forced by MPI-ESM. (16th March 2016) - Cheneka, Bedassa R.; Brienen, Susanne; Fröhlich, Kristina; Asharaf, Shakeel; Früh, Barbara
Abstract : Downscaling of seasonal hindcasts over East Africa with the regional climate model (RCM) COSMO-CLM (CCLM), forced by the global climate model (GCM) and MPI-ESM, is evaluated. The simulations are done for five months (May to September) for a ten-year period (2000–2009), with the evaluation performed only for June to September. The dry years, 2002 and 2009, and the wet years, 2006 and 2007, are well captured by the models. By using ground based and satellite gridded observation data for evaluation it is found that both COSMO-CLM and MPI-ESM overestimate June to September precipitation over the Ethiopian highlands and in parts of the lowland with respect to all reference datasets. In addition we investigated the potential and real added value for both the RCM and the GCM hindcasts by upscaling (arithmetic mean) the precipitation resolution both in temporal and in spatial scales, over North Ethiopia (EN), South Ethiopia (ES), South Sudan (SS), and Sudan (S). Results inferred that using the RCM for seasonal forecast adds value in capturing extreme precipitation years, especially in the Ethiopian highlands. It is also found that the potential and relative potential added value decrease with decreasing the temporal resolution.